Perancangan Tata Letak Vertikal Pembuatan Emping Melinjo - Guntarti Tatik Mulyati; Wagiman Wagiman; A.M. Madyana (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2004)
Melinjo crackers small-scale industries are among the industries which still adopt manual and traditional production processes. The research is aimed at improving layouts of a melinjo cracker small scale industry using workers' vertically anthropometrical data. The research was initiated by measuring the workers, productivity and observing the horizontal layouts before the modification. Anthropometrical data were collected by measuring the dimension of woman's body. Such data would be used to design the new layouts by considering then heights of equipment and of the workers 'sitting position. The results show that a better layout arrangement could be achieved. The workers worked by sitting on a chair with the heights of the table and the chair tailored to the worker's anthropometrical data. The position of the equipment was within the workers range of movements, the pealing and the crushing tools were within the normal working area, while the frying and the raw material were on the maximum working area. The workers felt more comfortable when doing their works.